Wild bird trafficking in Brazil and the veterinary physician’s activities - Carinhato, R. A. P.; Sanches, J. M.; Masseno, A. P. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
The Brazilian fauna has a high biodiversity, introducing about 10% of 1,400,000 animals catalogued on the planet (BRASIL, 2002). This data makes Brazil as a target country in the trade of wild animals. According to Rede Nacional Contra o Tráfico de Animais Silvestres ([2012?]) surveys, it was concluded that: About 80% of the smuggled animals are birds, moving around R 3 billion. Therefore, the large amount of money involved in the purchase of animals combined with the high level of poverty in certain regions of Brazil, is the reason that can promotes even more the illegal trade. In addition, the capture of wild animals is linked to the use of members of the fauna as pets, source of income and as food (FREITAS et al., 2015). An important point for the conservation of wild birds is the knowledge of the fauna that is kept illegally. It is necessary the analysis of the species, number of specimens, animal health conditions and the appropriate treatment to be performed to return them to the homeostasis. To all of these assumptions the Veterinarian is essential profession. After the rescue of these birds and their appropriated treatment, their main destination is returning them to the nature (RIBEIRO; SILVA, 2007). This paper performs an analysis of birds traffic in Brazil and discuss the importance of the veterinarians in the control of this practice.